1994
DOI: 10.1021/bk-1995-0582.ch020
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Antibiosis in Biocontrol of Plant Disease

Abstract: The implication of antibiotics and enzymes of fungal origin in biocontrol has been extensively investigated, but only in a few cases has their role been conclusively elucidated. Production of the antifungal epidithiadiketopiperazine metabolites chaetomin and gliotoxin by the soil-inhabiting biocontrol fungi, Chaetomium globosum and Gliocladium virens, respectively, has been shown to be of importance in biocontrol. Recently, the antifungal properties of purified chitinolytic and glucanolytic enzymes from the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…and plant parasitic nematodes (Siddiqui, Ehteshami-Haque & Ghaffer, 1999). Trichoderma species are known to produce secondary metabolites that act on the soil borne pathogens through parasitism and/or antibiosis (Belanger, Dufour, Caron & Benhamou, 1995;Di Pietro, 1995Cotes, Lepoivre & Semal, 1996. Waafa, Haaga and Amin (2001) also reported a reduction in fungal -nematode disease complex and an increase in plant growth parameters with the application of T. harzianum.…”
Section: Discussionmentioning
confidence: 99%
“…and plant parasitic nematodes (Siddiqui, Ehteshami-Haque & Ghaffer, 1999). Trichoderma species are known to produce secondary metabolites that act on the soil borne pathogens through parasitism and/or antibiosis (Belanger, Dufour, Caron & Benhamou, 1995;Di Pietro, 1995Cotes, Lepoivre & Semal, 1996. Waafa, Haaga and Amin (2001) also reported a reduction in fungal -nematode disease complex and an increase in plant growth parameters with the application of T. harzianum.…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma species are filamentous fungi which have been found to show potential as biological agents against seed and root rotting pathogens and for managing post harvest diseases (Okigbo and Ikediugwu, 2000). T. harzianum is known to produce extracellular cell wall degrading enzymes such as chitinases, β-1,3-glucanases and cellulases which are important features of mycoparasites for the colonization of their host fungi (Lorito et al, 1994;Di Pietro, 1995). Chet and Baker (1980) observed that soils that are naturally suppressible to R. solani contained a high A. niger T. harzianum B. cereus B. subtilis natural population of T. harzianum, while Strashnov et al (1985) reported that application of T. harzianum by coating tomato fruits reduced R. solani fruit rot by up to 85% under laboratory condition.…”
Section: Discussionmentioning
confidence: 99%
“…Several species of Trichoderma have been reported to suppress soil borne disease fungi included Fusarium and parasitic nematodes (Siddiqui et al, 1999). Trichoderma species are known to produce other secondary metabolites such as enzymes (Di Pietro, 1995). These enzymes in biocontrol can often assigned in both mechanism parasitism and antibiosis.…”
Section: Discussionmentioning
confidence: 99%